Hopelessness, Death Anxiety, and Social Support of Hospitalized Patients With Gynecologic Cancer and Their Caregivers. Issue 5 (September 2019) - Uslu-Sahan, Fatma; Terzioglu, Fusun; Koc, Gulten
Abstract : Background: Gynecologic cancer can create hopelessness and death anxiety and alter the lifestyle of the affected women and their caregivers. Perceived social support may facilitate coping with this illness. Objective: The aim of this study was to determine whether hospitalized patients with gynecologic cancer and their caregivers differ in feelings of hopelessness and death anxiety and how those conditions may be related to their social support. Methods: Two hundred patients with gynecologic cancer and their 200 caregivers from 1 university hospital were enrolled in this descriptive correlational study. Study measures included a demographic form, the Perceived Social Support Scale, the Beck Hopelessness Scale, and the Thorson-Powell's Death Anxiety Scale. Data were analyzed using Student t test, Pearson correlation test, and linear regression analyses. Results: Patients had higher hopelessness and death anxiety compared with caregivers ( P < .001). Patients' perceived social support explained 35% of the total variance in hopelessness and 28% of the variance in death anxiety; caregivers' perceived social support explained 40% of the total variance in hopelessness and 12% of the variance in death anxiety. Conclusion: Patients felt hopelessness and death anxiety in greater rates than caregivers. Social support had a significant effect on hopelessness and death anxiety of patients and their caregivers. Implications for Practice: Nurses, who are the healthcare professionals spending time with patients and families from diagnosis forward, need to evaluate patients and their caregivers for hopelessness and death anxiety and consider their social support systems during this evaluation.